Association of 77 polymorphisms in 52 candidate genes with blood pressure progression and incident hypertension: the Women's Genome Health Study - Conen, David; Cheng, Suzanne; Steiner, Lori L; Buring, Julie E; Ridker, Paul M; Zee, Robert Y L (Journal of hypertension, 2009)
Genetic risk factors for essential hypertension are largely unknown. The aim of the present study was to assess the association of 77 previously characterized gene variants in 52 candidate genes from various biological pathways with blood pressure (BP) progression and incident hypertension. We analyzed data from 18 738 white women who participated in a prospective cohort study and were free of hypertension at baseline. BP progression at 48 months and incident hypertension during the entire follow-up according to the different genotypes were assessed by logistic regression and Cox proportional-hazards models, respectively. At 48 months of follow-up, 7889 of 16 635 women (47.4%) had BP progression. Only three of 70 polymorphisms with a minor allele frequency of at least 2% had a significant association with BP progression. The odds ratio [95% confidence interval (CI)] for 5,10-methylenetetrahydrofolate reductase (MTHFR) rs1801133 (minor allele T), natriuretic peptide precursor A (NPPA) rs5063 (minor allele A) and NPPA rs5065 (minor allele C) were 1.05 (1.00-1.10), 0.84 (0.76-0.94) and 0.93 (0.88-1.00), respectively. After adjustment for multiple testing using the false discovery rate, only the NPPA rs5063 association remained significant. During a median follow-up of 9.8 years, 5540 of 18 738 women developed incident hypertension. Only five of 70 polymorphisms were significantly associated with incident hypertension. The hazard ratio (95% CI) for interleukin 6 (IL-6) rs1800795 (minor allele C), MTHFR rs1801133, NPPA rs5063, nitric oxide synthase 3 rs1799983 (minor allele T) and transforming growth factor, beta 1 rs1800469 (minor allele T) were 0.96 (0.92-1.00), 1.06 (1.02-1.10), 0.88 (0.80-0.96), 1.05 (1.01-1.09) and 1.05 (1.01-1.10), respectively. After adjustment for multiple testing, none of these associations remained significant. NPPA gene polymorphisms may have a role in BP progression and incident hypertension. Our data also provide moderate confirmatory evidence of association between MTHFR rs1801133 and the development of hypertension.